Pengaruh Pemahaman, Sikap, dan Kesadaran Wajib Pajak terhadap Kepatuhan Membayar Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) di Tapanuli Tengah - Frans Olsen Sitanggang (Neolectura, 2021)
Rural and Urban Land and Building (PBB-P2) Tax revenue always decreases every year, this result in obstruction of the development process, it is considered very necessary to be analyzed to find out what causes the decreases in the level of public compliance in paying PBB tax. The purpose of this study was to analyze the influence of understanding, attitudes and awareness of taxpayers partially and together to influence compliance in paying the Rural and Urban Land and Building Tax (PBB-P2) in Pandan District, Central Tapanuli Regency. The population is taxpayer in Pandan District amount 11.192 taxpayers. The sample in this study amounted to 99 taxpayers. Methods of data collection through questionnaires, interviews, and study documentation. Data analysis technique used aredescriptive statistics and multiple linear regression. The results showed that (1) the understanding variable is positive effect and significant to the compliance of taxpayers paying Land and Building Taxes for Rural and Office Buildings (PBB-P2) in Pandan District, (2) attitude variable is positive effect and significant to the compliance of taxpayers paying Land and Building Taxes for Rural and Office Buildings (PBB-P2) in Pandan District, (3)awareness variable is positive effect and significant to the compliance of taxpayers paying Land and Building Taxes for Rural and Office Buildings (PBB-P2) in Pandan District, (4) variables of understanding, attitudes and awareness of taxpayers together have a positive and significant effect on the tax compliance variable paying tax on Land and Building Taxes in Rural and Office Buildings (PBB-P2) in Pandan District. The test results of the coefficient of determination (R2) that the variable of understanding, attitude and awareness of taxpayers is able to explain the taxpayers' compliance to pay Land and Building Taxes for Rural and Office Buildings (PBB-P2) in Pandan Distric by 53.6 %. While the remaining 46.4% is explained by other factors not examined in this study.